lmpact of parasitoids in egg-batches of Thaumetopoea pityocampa (Den. & Schiff.) in Algeria (Bollettino di zoologia agraria e bachicoltura, 2024)
Twenty egg-batches of Thaumetopoea pityocampa (Den. & Schiff.) (Lep.: Thaumetopoeidae) collected in Algeria at Mt. Orest (1480-1550 mNN) in February 1993 were singled in test tubes with cotton stoppers and kept at 20-22°C. All batches were deposited in the fall of 1992, and exposed to the parasitoids during the whole developmental period of the host. Daily observations were made until May 1993, and on 25.Vlll.1993 after removing the egg scales. A final observation of the egg-batches was carried out on 21.Vl.1994. All eggs without a hole in the shell were opened carefully, and the meconia and remains were identified. The mean number of eggs per batch was 154, oviposited in 6-9 rows. In all cases, oviposition occurred from the base to tip of the needles. The hatching rate of caterpillars was 55.8%. The parasitoid impact on the total mortality was 76.1%. The most frequent egg-parasitoid was Baryscapus servadeii (Dom.) followed by Ooencyrtus pityocampae (Mercet). In one egg, multiparasitism could be observed. B. servadeii oviposited more frequently in later embryonic stages of the host than O. pityocampae. Most of the egg parasitoids emerged after a willter diapause, this was more noticeable in B. servadeii than in O. pityocampae. The latter had a shorter diapause period than the former. Only one male of each ooparasitoid species could be detected. The base and top of the egg-batches were preferred for parasitizing by B. servadeii, and only the basal part by O. pityocampae, inspite of many unscaled eggs being avialable in the middle part of the batches.
Keywords: Thaumetopoea pityocampa; egg parasitoids; Baryscapus servadeii; Ooencyrtus pityocampae; parasitism; host mortality; impact; Algeria